Is cystic fibrosis survival improving in excess to that of the general population for England and Wales and the USA?. (24th May 2012) - Hurley, MN; McKeever, T; Prayle, AP; Fogarty, A; Smyth, AR
Abstract : Aims: Cystic fibrosis (CF) is the commonest autosomal recessive, life-limiting condition in the developed world. CF survival is improving and current models predict a median survival over 50 years, for those born since 2000. It has been assumed that such improvements in survival have been due to improvements in care. We tested the alternative hypothesis that improvements in CF survival simply reflect improving life expectancy of the general population. Methods: Mortality data for each year by cause of death and gender were retrieved from the Office of National Statistics for England and Wales (1968-2009) and Centre of Disease Control WONDER for United States (1979-2007). Median age at death was interpolated for each group and for a sub-group analysis of childhood mortality (aged 1-19 years). The absolute difference between groups over time was calculated and a regression model constructed to explore the relationship between series over time. Results: The all-cause survival in England and Wales was better than that in the US over 5 decades. CF survival was better in the US compared to England and Wales and better for males compared to females in both countries. The difference in median survival between all-cause mortality and CF mortality is narrowing over time by between 0.26-0.36 life years per year (males in England and Wales difference coefficient −0.367; p<0.001) as is the difference in survival between those with CF in the US and those in England and Wales (difference coefficient, males −0.074; p=0.038). The difference in survival between males and females with CF does not appear to be reducing in either the US or England and Wales. These trends are mirrored in the childhood sub-group, although median age of childhood CF mortality is better than all-cause mortality post-1989. Conclusions: The steady increase in survival of those with CF cannot be accounted for simply by improvements in living conditions and health experienced by the general population but must in part be attributable to advances in the medical care of people with CF.